Effect of pulsed-laser and/or electron irradiation on vacancy diffusion in SUS316L austenitic stainless steel - YANG Su-bing; YANG Zhan-bing; WANG Hui (工程科学学报)
Electron irradiation and simultaneous pulsed-laser and electron dual-beam irradiation were performed using laser high voltage electronic microscopy (HVEM) at 500℃, and the void-denuded zone (VDZ) and radiation-induced segregation (RIS) near the random grain boundary were observed and analyzed after irradiation. Compared to electron irradiation, the effect of simultaneous pulsed-laser and electron dual-beam irradiation on vacancy diffusion was investigated. The results show that the width of VDZ after simultaneous pulsed-laser and electron dual-beam irradiation is 48 ±16 nm which is smaller than the VDZ width of 71 ±27 nm after electron irradiation. Both the magnitude and width of Cr and Ni segregation under simultaneous pulsed-laser and electron dual-beam irradiation are lower than those under electron irradiation. The ratio of vacancy flux of simultaneous pulsed-laser and electron dual-beam irradiation to that of electron irradiation is 45.7%. Compared to electron irradiation, the vacancy flux flowing into point defect sinks is lower owing to enhanced recombination between vacancies and interstitial spaces under simultaneous pulsed-laser and electron dualbeam irradiation. This has the effect of suppressing RIS and void swelling. Therefore, simultaneous pulsed-laser and electron dualbeam irradiation is expected to provide new insights into the suppression of void swelling.